Clinical Features and Genomic Characterization of Post-Colonoscopy Colorectal Cancer. Issue 10 (6th October 2020) - Tanaka, Hidenori; Urabe, Yuji; Oka, Shiro; Shimohara, Yasutsugu; Nishimura, Tomoyuki; Inagaki, Katsuaki; Okamoto, Yuki; Matsumoto, Kenta; Yamashita, Ken; Sumimoto, Kyoku; Ninomiya, Yuki; Yuge, Ryo; et al.
Abstract : INTRODUCTION: Some colorectal cancers (CRCs) may be missed during colonoscopies. We aimed to determine the clinicopathological, biological, and genomic characteristics of post-colonoscopy CRCs (PCCRCs). METHODS: Of the 1, 619 consecutive patients with 1, 765 CRCs detected between 2008 and 2016, 63 patients with 67 PCCRCs, when colonoscopies were performed 6–60 months before diagnosis, were recruited. After excluding patients with inflammatory bowel disease, familial polyposis syndrome, CRCs that developed from diminutive adenomatous polyps, and recurrent CRCs after endoscopic resection, 32 patients with 34 PCCRCs were enrolled. The lesions' clinicopathological features, mismatch repair proteins (MMRs), and genomic alterations were investigated. RESULTS: The overall PCCRC-5y rate, rate of intramucosal (Tis) lesions, and rate of T1 or more deeply invasive cancers were 3.7% (66/1, 764), 3.9% (32/820), and 3.6% (34/944), respectively. Thirty-three patients' MMRs were investigated; 7 (21%) exhibited deficient MMRs (dMMRs), comprising 4 with T2 or more deeply invasive cancers and 5 whose lesions were in the proximal colon. Twenty-three tumors' genomic mutations were investigated; PIK3CA had mutated in 5 of 6 T2 or more deeply invasive cancers, of which, 4 were located in the proximal colon. Two patients with dMMRs and BRAF V600E mutations had poor prognoses. Sixty-one percent (17/28) of the macroscopic type 0 lesions were superficial. All superficial Tis and T1 PCCRCs were detected <24 months after the negative colonoscopies. They were distributed throughout the colon and rectum. DISCUSSION: PCCRCs may be invasive cancers in the proximal colon that exhibit dMMRs and/or PIK3CA mutations or missed early CRCs especially superficial lesions.